High-risk human papillomavirus genotypes among women of hill districts in Bangladesh - Ashrafun Nessa; Jannatul Ferdouse; Farhana Khatoon; Asma Akhter Sonia; Md Foyjul Islam; Lutfa Begum Lipi (PLoS ONE, 2025)
Knowledge on the distribution of type specific HPV (Human papillomavirus) genotypes in female cervix is crucial to identify women who are at a higher risk of developing cancer. This study aimed to find out the prevalence of High-risk HPV genotypes among women of three Hill districts of Bangladesh. This cross-sectional study was conducted between 1st January and 30th June 2024 among 1602 selected married asymptomatic tribal and nontribal women (30–60 years of age) at three Hill districts. Partial genotyping of HPV DNA specimens which detects the presence of 14 high-risk genotypes (including individual HPV-16, HPV-18, and others as a pooled group) was performed at Bangladesh Medical University (BMU). Women with previous treatment of cervical precancer and cancer, hysterectomy, cervical amputation and pregnancy were excluded. Statistical analysis utilized SPSS version 25.0, employing Chi-square and Fisher’s Exact tests and P value <0.05 were considered significant. HR-HPV prevalence’s were expressed as proportions. The influence of HR-HPV infection and socio-demographic factors was assessed using multinomial logistic regression analysis. The overall HR-HPV prevalence was 2.7% (n = 44) and 0.8% (n = 13) were tested positive for HPV16, 0.2% (n = 4) for HPV18 and 1.6% (n = 26) for ‘Other HR-HPV’ types. No significant difference of HR-HPV prevalence was observed among the three districts (p-value = 0.352) and among tribal (2.4%) and non-tribal/Bengali (3.2%) women (p-value>0.05). Higher number of marriages of the husbands have independent association with HR-HPV positivity showing an odds ratio of 2.02 (95% CI: 1.07–3.82, p = 0.030). The HR-HPV prevalence in hill districts of Bangladesh is low with independent association of higher number of marriages of the husbands with HR-HPV positivity. These findings may guide policymakers to initiate HR-HPV DNA-based screening and reconsider vaccination strategies in the hill areas, including the introduction of gender-neutral vaccination.